Universal Padé аpproximants with respect to the chordal metric - V. Nestoridis (Հայաստանի ԳԱԱ)
The use of the chordal distance does not change the notion of Universal Taylor series. However, it changes the notion of Universal Pade approximants. Using Pade approximants of meromorphic or holomorphic functions we can approximate all rational functions on compact sets of arbitrary connectivity.
Keywords: Mathematics; Science; General Works